ARTISTIC IMAGE AS A REFLECTION THE PROCESS OF SOCIALIZATION OF PERSONALITY - O.Ch. Chyrva (Academy of Cognitive and Natural Sciences, 2006)
The article deals with the problem of en image as a semiotic unit of visual communication and its functional ability during persons socialization through the common function of culture.